Improving Insurance Protection for Rare Diseases: Economic Burden and Policy Effects - Simulation of People With Pompe Disease in China - Shanquan Chen; Dong Dong (Kerman University of Medical Sciences, 2023)
Background  The economic burden of Pompe disease (PD) is under-researched. This study aimed to fill this gap and provide evidence-based suggestions for policy improvement based on policy simulation.Methods  Data were derived from a nationally based cross-sectional survey on rare diseases in early 2018. Answers from 92 PD patients were used for data analysis and simulation. Catastrophic health expenditure (CHE) and impoverishment due to illness (IDI) were adopted to measure PD patients' economic burden. Two typical reimbursement patterns, a dosage-based model and a cost-based model, in China were simulated.Results  Twenty-four pediatric and 68 adult PD patients were investigated. Families with pediatric PD patients on average had lower annual household incomes than families with adult PD patients (RMB 37 890 vs. RMB 66 120). The direct medical expense and out-of-pocket expenses were almost double for pediatric patients compared with adult patients (RMB 120 050 vs. RMB 66 350; RMB 112 710 vs. RMB 57 940, respectively). The direct non-medical expense for patients was almost six times the expense of adult patients (RMB 73 790 vs. RMB 13 080, respectively). About 88.24% of families with pediatric PD patients and 67.21% of families with adult PD patients suffered from CHE. Around 84.21% of families with pediatric PD patients and 45.90% of families with adult PD patients were forced to live in poverty due to illness. The simulation indicated that, although the two current reimbursement schemes helped reduce CHE, they almost had no effect on reducing IDI; the dosage-based model was more sensitive to changes in policy parameters.Conclusion  Our study highlighted the alarmingly high disease burden faced by PD patients with first-hand patientreported evidence. Our series of simulations could be a good reference for China and other countries to improve their reimbursement policy regarding PD.